Safety effects of traffic lane and shoulder widths on two-lane undivided rural roads: A matched case-control study from Norway. (September 2020) - Pokorny, Petr; Jensen, Jan K.; Gross, Frank; Pitera, Kelly
Highlights: Sample of 71, 999 roadway segments of rural two-lane roads was identified with GIS. Models calculated separately for winter/non-winter and severe/slight accidents. A non-monotonous link between risk and shoulder width categories. An increased risk corresponds with increasing lane width categories. Abstract: This study estimates the effects of lane and shoulder widths on occurrence of head-on and single-vehicle accidents on rural two-lane undivided roads in Norway while considering the differences between winter and non-winter accidents and their severity levels. A matched case-control method was applied to calculate the odds ratios for lane and shoulder width categories, while controlling for the effects of AADT and adjusting for the effects of region, speed limit, segment length, share of long vehicles in AADT and horizontal alignment. The study used a sample of 71, 999 roadway segments identified in GIS and 1886 related accidents recorded by the police in five-year period. The results suggest that it is relevant to consider winter and non-winter accidents as well as severe and slight accidents separately when studying the effects of lane and shoulder widths on the occurrence of head-on and single-vehicle accidents. When examining lane and shoulder widths for all related accidents, the lane widths 1.50–2.50 m and shoulder widths 0.50−0.75 m were relatively safer than other categories on Norwegian two-lane rural undivided roads.